The Influence of Contextual Teaching and Learning (CTL) Model on Learning Outcomes in Colloid System Material at Class XI Madrasah Aliyah Negeri 2 Model - Nurhayati, Fitri; Mustapa, Kasmudin; Jura, Minarni Rama (Jurnal Akademika Kimia, 2019)
This study aimed to determine students’ learning outcomes in Grade X at MA Yayasan Islam Indonesia Pulau Sebatik by applying cooperative learning model-Jigsaw type on the hydrocarbons material. This type of study was a quasi-experimental research with non-randomized pretest-posttest control group design. The population in this study was students of class X MA YIIPS academic year 2014/2015 which amounted of 42 students and consisted of 2 classes. The sample in this study was class XA MA YIIPS (n = 22) as the experiment class and class XB MA YIPS (n = 22) as the control class. The result of data analysis in the experiment class obtained X̅1 value of 78.81 with a standard deviation of 10.41, and in the control class obtained X̅2 value was 70.72 with a standard deviation of 11.55. The result of hypothesis test was tcount > ttable (8.17 > 1.67) with significant level (α) of 0.05 and degree of freedom of 42. This result indicated that H0 was rejected and H1 was accepted, so it can be concluded that the students’ learning outcomes of chemistry on the hydrocarbons material treated with cooperative learning model-Jigsaw type is better than untreated class.